The Unusual Case of Fibroma of Tendon Sheath in a Young Girl with Turner Syndrome Undergoing Growth Hormone Treatment - Yong Hee Hong; Dong Gyu Kim; Jong Hyun Lee; Min Jung Jung; Chang Yong Choi (Galenos Yayincilik, 2021)
Fibroma of tendon sheath (FTS) is an uncommon mass that arises from the tendon sheath of extremities. The tumor typically affects adults between ages 20 and 50 years with a predominance in males. To date, growth hormone (GH) treatment is safe for children with Turner syndrome without risk factors and is accepted worldwide. This article reports the case of a nine-year-old female patient with Turner syndrome and FTS during GH treatment. She had been treated with daily subcutaneous GH to improve growth failure with a mean dose of 0.28 mg/kg/week and the level of insulin-like growth factor-1 was within the normal range. During the follow-up period, she complained about a mass in her hand, subsequently diagnosed as FTS. This report illustrates the clinical impact of Turner syndrome and GH treatments on the occurrence of this tumor through literature reviews. Further studies are needed to highlight the association between FTS and GH treatment, especially in Turner syndrome.